2014
DOI: 10.4310/jsg.2014.v12.n1.a5
|View full text |Cite
|
Sign up to set email alerts
|

Analytic test configurations and geodesic rays

Abstract: Starting with the data of a curve of singularity types, we use the Legendre transform to construct weak geodesic rays in the space of locally bounded metrics on an ample line bundle L over a compact manifold. Using this we associate weak geodesics to suitable filtrations of the algebra of sections of L. In particular this works for the natural filtration coming from an algebraic test configuration, and we show how this recovers the weak geodesic ray of Phong-Sturm.Theorem 1.2. Suppose that F k,λ is left contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
132
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(132 citation statements)
references
References 38 publications
0
132
0
Order By: Relevance
“…Let ω be the Fubini-Study metric on X = P 1 , normalized to mass 1. A compact, polar Cantor set K ⊂ P 1 carries a natural probability measure without atoms, and the potential u of this measure with respect to ω is smooth outside K, has zero Lelong numbers and does not belong to E. By [RWN14,Dar17b], u defines a locally bounded weak geodesic ray (u t ) emanating from 0 such that E(u t ) = at with a < 0. However, the corresponding ω-psh function U on X × D has zero Lelong numbers, hence U NA = 0 and E NA (U NA ) = 0. where we have set as before λ = V −1 (K X · L n−1 ).…”
Section: 3mentioning
confidence: 99%
“…Let ω be the Fubini-Study metric on X = P 1 , normalized to mass 1. A compact, polar Cantor set K ⊂ P 1 carries a natural probability measure without atoms, and the potential u of this measure with respect to ω is smooth outside K, has zero Lelong numbers and does not belong to E. By [RWN14,Dar17b], u defines a locally bounded weak geodesic ray (u t ) emanating from 0 such that E(u t ) = at with a < 0. However, the corresponding ω-psh function U on X × D has zero Lelong numbers, hence U NA = 0 and E NA (U NA ) = 0. where we have set as before λ = V −1 (K X · L n−1 ).…”
Section: 3mentioning
confidence: 99%
“…6.1]. In [37,Rmk. 6.11], the authors speculate that ϕ 1 should be in C 1,α loc for all α < 1, and actually prove that it is in C 1,1 loc when X = CP 1 , using either the results of [18] or [10].…”
Section: Introductionmentioning
confidence: 99%
“…We thus show that this stronger result indeed always holds. As a corollary, one can now apply [37,Cor 6.7] to the Hele-Shaw flow on a general Riemann surface X to see that it is always strictly increasing at at least some fixed positive rate.…”
Section: Introductionmentioning
confidence: 99%
“…Given their importance in the above mentioned applications, we are interested to see how one can construct weak geodesic rays inside (E 1 (X, θ), d 1 ), with the hopes of using them in later investigations involving big cohomology classes. To this end, we point out below that the construction of Ross and Witt Nyström [RWN14] not only generalizes to the big case, but it can be shown that their very flexible method gives all possible weak geodesic rays (with minimal singularity) in a unique manner.…”
Section: Introductionmentioning
confidence: 99%
“…Section 3 is devoted to the proof of Theorem 1.1. In Section 4 we adapt the concepts of [RWN14] to the big context and prove Thoerem 1.2 and Corollary 1.3.…”
Section: Introductionmentioning
confidence: 99%